Caught in the Machinery: Workplace Accidents and Injured Workers in Nineteenth-Century Britain - Tucker, Eric (Labour / Le Travail, 2008)
The article reviews the book, "Caught in the Machinery: Workplace Accidents and Injured Workers in Nineteenth-Century Britain," by Jamie L. Bronstein.
Keywords: BOOKS -- Reviews; BRONSTEIN, Jamie L.; CAUGHT in the Machinery: Workplace Accidents & Injured Workers in 19th-Century Britain (Book); Nonfiction; WORK-related injuries